ATTRACTIVENESS OF THE OLD TOWN TO STRENGTHEN THE IMAGE OF THE CITY OF SEMARANG - Nugraheni, Christanti; Nurhikmah Budi Hartanti (International Journal on Livable Space, 2023)
A good city must have a city Image where the perception of the city image is based on the process of observation, memory, attitude, and feelings that are directly created. The Old City as an urban heritage destination has its charm for visitors to the city of Semarang, which in turn has contributed to the image of the city of Semarang. This study aims to determine how the attractiveness of the old city strengthens the image of Semarang City and what factors support. This can promote the physical and non-physical sustainability of the old city, so that people get to know the city of Semarang through the old city. The results of this study found that the Old City of Semarang contributed to the formation of the image of the city of Semarang but was not too strong. This is influenced by the attractiveness of the old city which is visually different from its surroundings where the forming elements have a strong characteristic. Keywords: City Image, Attractiveness, Old Town